PEMBERDAYAAN IBU PKK MELALUI PEMBUATAN HIDROPONIK RAMAH LINGKUNGAN DI DUSUN JETIS PASURUAN - Nabillah Rochmatan Lil’alamin; Ries Dyah Fitriyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Jetis Hamlet in Prodo Village, Winongan District, Pasuruan Regency, has great agricultural potential in rice and corn cultivation, but is often threatened by flooding due to its location between two rivers. To overcome this, the hydroponic system was introduced as an innovative solution. Hydroponic training using the Wick System method was given to PKK mothers. This training aims to improve their skills in hydroponic farming which is more efficient, environmentally friendly, and flood-resistant, as well as helping to improve community welfare and food security. The research conducted on the PKK Mothers group in Jetis Hamlet, Pasuruan used the Asset Based Community Development (ABCD) approach. This approach emphasizes the utilization of assets owned by the community. As a result, PKK mothers were able to implement a hydroponic system at home, increase agricultural productivity, food security, and family income amidst the threat of flooding, and support sustainable local economic development.